Absolute Unity in the Philosophy of IbnSaba'in Al-Mursi, a reading in the book "Bad Al-Arif - kab, hatem (El Omda in Linguistics and Discourse Analysis, 2022)
The attempt to trace the influence of the Andalusian scholarly elite who migrated to Algeria is of paramount importance in outlining the contours of Islamic Sufism in Morocco and Andalusia. This exploration reveals numerous significant achievements in the historical development of science and knowledge in our lands. It is worth noting that mystical Sufism, in particular, occupied a prominent place in the writings of Moroccan and Andalusian Sufis from its earliest forms with Ibn Masarra in the 4th century AH, through the 7th-century Sufis such as Ibn Arabi, Afif al-Din al-Tilimsani, al-Shushtari, Ibn Sab'in, and others. During these periods, it manifested itself on multiple levels, oscillating between Sharia (Islamic law) and Haqiqah (Sufi truth), and between religion and philosophy. As a contribution to revealing the patterns of this Sufism, we try to monitor some of its sayings through the text of “The Beginning of the Knower” by its author Ibn Dara, known as Ibn Sab’in, who filled the world and occupied people through what he presents of a Sufi philosophy that enshrines the saying of absolute unity, through his various travels, including “The Beginning of the Knower.” This belief sees only one reality for this universe, which is: the Truth. For him, the universe is one, which is the Truth, as Ibn Sab’in sees that the existence of creatures is the same as the existence of the Truth, and that this multiplicity that occurs in the universe does not exist in reality. For this reason, his theory of absolute unity came as strange and closed to minds, which aroused scholars and jurists against it. Accordingly, this approach is based on a fundamental epistemological question that we can formulate as follows: How did the book “Bad al-Arif” contribute to bringing closer the theory of absolute unity in Ibn Sab’in, and defining the features of his method in knowledge and interpretation?? And more importantly, how can this pivotal statement/absolute unity reflect the close ties that Ibn Sab’in’s philosophical Sufism links with many of the Sufi masters in Tlemcen, such as Sheikh Afif al-Din, Sheikh al-Shawdhi, his student Ibn al-Mar’a, Ibn Ahla al-Tilimsani, and others? The attempt to trace the influence of the Andalusian scholarly elite who migrated to Algeria is of paramount importance in outlining the contours of Islamic Sufism in Morocco and Andalusia. This exploration reveals numerous significant achievements in the historical development of science and knowledge in our lands. It is worth noting that mystical Sufism, in particular, occupied a prominent place in the writings of Moroccan and Andalusian Sufis from its earliest forms with Ibn Masarra in the 4th century AH, through the 7th-century Sufis such as Ibn Arabi, Afif al-Din al-Tilimsani, al-Shushtari, Ibn Sab'in, and others. During these periods, it manifested itself on multiple levels, oscillating between Sharia (Islamic law) and Haqiqah (Sufi truth), and between religion and philosophy. As a contribution to revealing the patterns of this Sufism, we try to monitor some of its sayings through the text of “The Beginning of the Knower” by its author Ibn Dara, known as Ibn Sab’in, who filled the world and occupied people through what he presents of a Sufi philosophy that enshrines the saying of absolute unity, through his various travels, including “The Beginning of the Knower.” This belief sees only one reality for this universe, which is: the Truth. For him, the universe is one, which is the Truth, as Ibn Sab’in sees that the existence of creatures is the same as the existence of the Truth, and that this multiplicity that occurs in the universe does not exist in reality. For this reason, his theory of absolute unity came as strange and closed to minds, which aroused scholars and jurists against it. Accordingly, this approach is based on a fundamental epistemological question that we can formulate as follows: How did the book “Bad al-Arif” contribute to bringing closer the theory of absolute unity in Ibn Sab’in, and defining the features of his method in knowledge and interpretation?? And more importantly, how can this pivotal statement/absolute unity reflect the close ties that Ibn Sab’in’s philosophical Sufism links with many of the Sufi masters in Tlemcen, such as Sheikh Afif al-Din, Sheikh al-Shawdhi, his student Ibn al-Mar’a, Ibn Ahla al-Tilimsani, and others? The attempt to trace the influence of the Andalusian scholarly elite who migrated to Algeria is of paramount importance in outlining the contours of Islamic Sufism in Morocco and Andalusia. This exploration reveals numerous significant achievements in the historical development of science and knowledge in our lands. It is worth noting that mystical Sufism, in particular, occupied a prominent place in the writings of Moroccan and Andalusian Sufis from its earliest forms with Ibn Masarra in the 4th century AH, through the 7th-century Sufis such as Ibn Arabi, Afif al-Din al-Tilimsani, al-Shushtari, Ibn Sab'in, and others. During these periods, it manifested itself on multiple levels, oscillating between Sharia (Islamic law) and Haqiqah (Sufi truth), and between religion and philosophy. As a contribution to revealing the patterns of this Sufism, we try to monitor some of its sayings through the text of “The Beginning of the Knower” by its author Ibn Dara, known as Ibn Sab’in, who filled the world and occupied people through what he presents of a Sufi philosophy that enshrines the saying of absolute unity, through his various travels, including “The Beginning of the Knower.” This belief sees only one reality for this universe, which is: the Truth. For him, the universe is one, which is the Truth, as Ibn Sab’in sees that the existence of creatures is the same as the existence of the Truth, and that this multiplicity that occurs in the universe does not exist in reality. For this reason, his theory of absolute unity came as strange and closed to minds, which aroused scholars and jurists against it. Accordingly, this approach is based on a fundamental epistemological question that we can formulate as follows: How did the book “Bad al-Arif” contribute to bringing closer the theory of absolute unity in Ibn Sab’in, and defining the features of his method in knowledge and interpretation?? And more importantly, how can this pivotal statement/absolute unity reflect the close ties that Ibn Sab’in’s philosophical Sufism links with many of the Sufi masters in Tlemcen, such as Sheikh Afif al-Din, Sheikh al-Shawdhi, his student Ibn al-Mar’a, Ibn Ahla al-Tilimsani, and others? <div class="aJIq1d" dir="ltr" data-language-code="en" data-language-name="Anglais" data-text="The attempt to trace the influence of the Andalusian scholarly elite who migrated to Algeria is of paramount importance in outlining the contours of Islamic Sufism in Morocco and Andalusia. This exploration reveals numerous significant achievements in the historical development of science and knowledge in our lands. It is worth noting that mystical Sufism, in particular, occupied a prominent place in the writings of Moroccan and Andalusian Sufis from its earliest forms with Ibn Masarra in the 4th century AH, through the 7th-century Sufis such as Ibn Arabi, Afif al-Din al-Tilimsani, al-Shushtari, Ibn Sab'in, and others. During these periods, it manifested itself on multiple levels, oscillating between Sharia (Islamic law) and Haqiqah (Sufi truth), and between religion and philosophy. As a contribution to revealing the patterns of this Sufism, we try to monitor some of its sayings through the text of “The Beginning of the Knower” by its author Ibn Dara, known as Ibn Sab’in, who filled the world and occupied people through what he presents of a Sufi philosophy that enshrines the saying of absolute unity, through his various travels, including “The Beginning of the Knower.” This belief sees only one reality for this universe, which is: the Truth. For him, the universe is one, which is the Truth, as Ibn Sab’in sees that the existence of creatures is the same as the existence of the Truth, and that this multiplicity that occurs in the universe does not exist in reality. For this reason, his theory of absolute unity came as strange and closed to minds, which aroused scholars and jurists against it. Accordingly, this approach is based on a fundamental epistemological question that we can formulate as follows: How did the book “Bad al-Arif” contribute to bringing closer the theory of absolute unity in Ibn Sab’in, and defining the features of his method in knowledge and interpretation?? And more importantly, how can this pivotal statement/absolute unity reflect the close ties that Ibn Sab’in’s philosophical Sufism links with many of the Sufi masters in Tlemcen, such as Sheikh Afif al-Din, Sheikh al-Shawdhi, his student Ibn al-Mar’a, Ibn Ahla al-Tilimsani, and others?" data-crosslingual-hint="" data-location="2" data-enable-toggle-playback-speed="true" data-results-count="1" data-result-index="1"> <div class="aJIq1d" dir="ltr" data-language-code="en" data-language-name="Anglais" data-text="The attempt to trace the influence of the Andalusian scholarly elite who migrated to Algeria is of paramount importance in outlining the contours of Islamic Sufism in Morocco and Andalusia. This exploration reveals numerous significant achievements in the historical development of science and knowledge in our lands. It is worth noting that mystical Sufism, in particular, occupied a prominent place in the writings of Moroccan and Andalusian Sufis from its earliest forms with Ibn Masarra in the 4th century AH, through the 7th-century Sufis such as Ibn Arabi, Afif al-Din al-Tilimsani, al-Shushtari, Ibn Sab'in, and others. During these periods, it manifested itself on multiple levels, oscillating between Sharia (Islamic law) and Haqiqah (Sufi truth), and between religion and philosophy. As a contribution to revealing the patterns of this Sufism, we try to monitor some of its sayings through the text of “The Beginning of the Knower” by its author Ibn Dara, known as Ibn Sab’in, who filled the world and occupied people through what he presents of a Sufi philosophy that enshrines the saying of absolute unity, through his various travels, including “The Beginning of the Knower.” This belief sees only one reality for this universe, which is: the Truth. For him, the universe is one, which is the Truth, as Ibn Sab’in sees that the existence of creatures is the same as the existence of the Truth, and that this multiplicity that occurs in the universe does not exist in reality. For this reason, his theory of absolute unity came as strange and closed to minds, which aroused scholars and jurists against it. Accordingly, this approach is based on a fundamental epistemological question that we can formulate as follows: How did the book “Bad al-Arif” contribute to bringing closer the theory of absolute unity in Ibn Sab’in, and defining the features of his method in knowledge and interpretation?? And more importantly, how can this pivotal statement/absolute unity reflect the close ties that Ibn Sab’in’s philosophical Sufism links with many of the Sufi masters in Tlemcen, such as Sheikh Afif al-Din, Sheikh al-Shawdhi, his student Ibn al-Mar’a, Ibn Ahla al-Tilimsani, and others?" data-crosslingual-hint="" data-location="2" data-enable-toggle-playback-speed="true" data-results-count="1" data-result-index="1"> <div class="aJIq1d" dir="ltr" data-language-code="en" data-language-name="Anglais" data-text="The attempt to trace the influence of the Andalusian scholarly elite who migrated to Algeria is of paramount importance in outlining the contours of Islamic Sufism in Morocco and Andalusia. This exploration reveals numerous significant achievements in the historical development of science and knowledge in our lands. It is worth noting that mystical Sufism, in particular, occupied a prominent place in the writings of Moroccan and Andalusian Sufis from its earliest forms with Ibn Masarra in the 4th century AH, through the 7th-century Sufis such as Ibn Arabi, Afif al-Din al-Tilimsani, al-Shushtari, Ibn Sab'in, and others. During these periods, it manifested itself on multiple levels, oscillating between Sharia (Islamic law) and Haqiqah (Sufi truth), and between religion and philosophy. As a contribution to revealing the patterns of this Sufism, we try to monitor some of its sayings through the text of “The Beginning of the Knower” by its author Ibn Dara, known as Ibn Sab’in, who filled the world and occupied people through what he presents of a Sufi philosophy that enshrines the saying of absolute unity, through his various travels, including “The Beginning of the Knower.” This belief sees only one reality for this universe, which is: the Truth. For him, the universe is one, which is the Truth, as Ibn Sab’in sees that the existence of creatures is the same as the existence of the Truth, and that this multiplicity that occurs in the universe does not exist in reality. For this reason, his theory of absolute unity came as strange and closed to minds, which aroused scholars and jurists against it. Accordingly, this approach is based on a fundamental epistemological question that we can formulate as follows: How did the book “Bad al-Arif” contribute to bringing closer the theory of absolute unity in Ibn Sab’in, and defining the features of his method in knowledge and interpretation?? And more importantly, how can this pivotal statement/absolute unity reflect the close ties that Ibn Sab’in’s philosophical Sufism links with many of the Sufi masters in Tlemcen, such as Sheikh Afif al-Din, Sheikh al-Shawdhi, his student Ibn al-Mar’a, Ibn Ahla al-Tilimsani, and others?" data-crosslingual-hint="" data-location="2" data-enable-toggle-playback-speed="true" data-results-count="1" data-result-index="1">